IMPLEMENTATION OF BLENDED LEARNING THROUGH VIRTUAL CLASSROOM IN ENGLISH GRAMMAR COURSES - Muhamad Taufik Hidayat (English Education and Applied Linguistics Journal (EEAL Journal), 2019)
The development of information and communication technology that is growing rapidly offers challenges to the world of education so that it can be used for the advancement of education. This study aims to determine the effectiveness of the use of the concept of blended learning through virtual classrooms based on educational social networks in the English grammar course. This research used quantitative approach in answering the research questions. A total of 30 students will be used as research samples from all 168 students enrolled in the English grammar V course. Experimental research will serve as the main design of this study. The results of this study are expected to reveal the benefits of implementing the blended learning system through virtual classroom-based educational social networks in the English grammar course.